2015
DOI: 10.1039/c5ra07567j
|View full text |Cite
|
Sign up to set email alerts
|

Is a medium-range order pre-peak possible for ionic liquids without an aliphatic chain?

Abstract: The combination of amino acids anions with a choline cation gives origin to a new and potentially important class of organic ionic liquids that might represent a viable and bio-compatible alternative with respect to the traditional ones. We present here a combined experimental and theoretical study of a choline-proline ionic liquid, using both large and small angle X-ray diffraction (WAXS-SAXS), and classical and ab initio molecular dynamics calculations, in which we are able to point out for the first time th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In the first investigation, Benedetto et al (Benedetto et al 2014) described in detail the cation-anion interaction with DFT methods in vacuo and in small clusters containing up to four ion pairs, for eight amino acid anions (Ala, Val, Ser, Cys, Asp, Asn, Phe, His). In some later reports (Campetella et al 2015a(Campetella et al , b, 2016a(Campetella et al , b, c, 2017(Campetella et al , 2018, the presence of strong ion pairing was confirmed in larger models of the liquid phase (32 ion pairs). In one of these studies on cholinealanine (Campetella et al 2015a(Campetella et al , 2015b, infrared spectroscopy was chosen as experimental technique to support the computational results.…”
Section: Structural Featuresmentioning
confidence: 76%
See 1 more Smart Citation
“…In the first investigation, Benedetto et al (Benedetto et al 2014) described in detail the cation-anion interaction with DFT methods in vacuo and in small clusters containing up to four ion pairs, for eight amino acid anions (Ala, Val, Ser, Cys, Asp, Asn, Phe, His). In some later reports (Campetella et al 2015a(Campetella et al , b, 2016a(Campetella et al , b, c, 2017(Campetella et al , 2018, the presence of strong ion pairing was confirmed in larger models of the liquid phase (32 ion pairs). In one of these studies on cholinealanine (Campetella et al 2015a(Campetella et al , 2015b, infrared spectroscopy was chosen as experimental technique to support the computational results.…”
Section: Structural Featuresmentioning
confidence: 76%
“…In some later reports (Campetella et al 2015a(Campetella et al , b, 2016a(Campetella et al , b, c, 2017(Campetella et al , 2018, the presence of strong ion pairing was confirmed in larger models of the liquid phase (32 ion pairs). In one of these studies on cholinealanine (Campetella et al 2015a(Campetella et al , 2015b, infrared spectroscopy was chosen as experimental technique to support the computational results. The huge red shift (Δυ=900-1000 cm −1 ) of hydroxyl stretching vibration observed in the experiment was correctly reproduced by the model and was interpreted by calculating the Wannier centers along the AIMD trajectory, as due to the large number of different conformations and energies experienced during the simulation by the hydrogen bond-mediated pairs.…”
Section: Structural Featuresmentioning
confidence: 76%
“…Unfortunately, due to the wat-IL interaction, this kind of interaction is not sufficient to establish long range aggregation phenomena, as shown for the neat liquid in previous works. 36,39 To better characterize the H-bond network of the simulated boxes, we have extracted the H-bonds contacts lifetime from the trajectories. For the calculation, we exploited the autocorrelation function tool of TRAVIS, 40…”
Section: Resultsmentioning
confidence: 99%
“…From the earliest computational studies, it was clear that the ChAAILs structure was not as simple as initially thought. In particular, the emergence of low-Q peaks in the X-ray diffraction patterns seemed to indicate some kind of aggregation phenomena at the nanoscale which previous calculations on isolated dimers were not able to grasp (Campetella et al 2015b(Campetella et al , 2016b. The authors of these studies focused on Proand Phe-based ChAAILs where the presence of structured side chains could induce and enhance the formation of transient structures at the nanoscopic level.…”
Section: Structure and Computational Studiesmentioning
confidence: 99%